Effect of hot drying on the chemical content and colour sensory quality of ginger powder (Zingiber officinale) - Quang, Dao Nhat; Huong, Vu Thi; Tuan, Hoang Quoc (Vietnam Journal of Science and Technology, 2016)
The main objective of this study was to investigate the effect of different temperature of hot air drying on the qualities of ginger powder included chemical content, colour parameters and colour sensory quality. The drying experiments were carried out at four air temperature of 50, 60, 70 and 80oC. The colour parameters for colour change of the materials were quantified by the Hunter L (whiteness/darkness), a (redness/greenness) and b (yellowness/blueness) system. These values were also used for calculation of total change (DE). A consumer preference test was conducted with 80 consumers to assess the colour quality of 04 ginger powders. The results showed that the decreasing of essential oils content at low drying temperature is higher than at high temperature. While the fats content was significantly decreased during drying at high temperature as compared with low temperature due to oxidation process of fat occurring at high temperature. The ginger powder was dried at high temperature showed a highly reduced content of protein and carbohydrate. Least Squares regression was used to determine the relationship between colour sensory scores of consumer taster and quantification of three Hunter parameters. In that, variable “L” and “b” could be distributed to increasing while variable “a” contributory decrease the colour quality of ginger powder products. The zero-order, first-order and quadratic models were used to explain the colour change kinietics during hot drying ginger slices at 50oC and it was observed that L, b and a were fitted to quadratic model.